FAKTOR PENYEBAB BERKURANGNYA JUMLAH PEGUNJUNG OBJEK WISATA TAMAN MUKO-MUKO KECAMATAN TANJUNG RAYA KABUPATEN AGAM PROVINSI SUMATERA BARAT - Shinta Febria Wahyuni; Rahmanelli Rahmanelli (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
This study aims to determine: 1) The development of the number of visitors to the Muko-Muko Park tourism object and the position of the tourist attraction based on the Tourism Area Life Cycle (TALC) theory, 2) Physical factors that cause the reduction in the number of visitors to the Muko-Muko Park tourist attraction, Tanjung Raya District, 3 ) Social factors cause the decrease in the number of visitors to the Muko-Muko Park tourist attraction, Tanjung Raya District. This type of research is classified as Mix Methods. The number of subjects was 14 people. Data collection using questionnaires and interviews. The data analysis used was two approaches, namely qualitative and quantitative approaches. The results of this study are: 1) There was a very significant decrease in the number of visitors from 2017-2019 for domestic tourists as many as 35,345 people (-26.6%) in 2018 and in 2019 as many as 40,934 people (-42%), while tourists decreased from 2016 to 2019, namely 2,571 people (-38.3%) in 2017, 3,613 people (-87.3%) in 2018 and 432 people (-81.9%) in 2019. Based on the theory of Tourism Area Life Cycle (TALC), the tourist attraction of Muko-Muko Park is at a decline stage, 2) Physical factors cause the decrease in the number of visitors to the Muko-Muko Park tourist attraction due to the lack of facilities available at the tourist attraction, 3) Social factors are not the cause of the decrease the number of visitors to the tourist attraction Muko-Muko